النمذجة الخرائطية لتقدير حجم التعرية المائية لحوض وادي كاي براخ بطريقة جافريلوفيك باستعمال تقنيتي الاستشعار عن بعد ونظم المعلومات الجغرافية - الحميري، محمد عباس جابر (جامعة ميسان - كلية التربية, 2024)
يهدف البحث إلى استعمال معطيات الاستشعار عن بعد وبرمجيات نظم المعلومات الجغرافية لنمذجة خرائط تقدير حجم التعرية المائية وفق طريقة جافريلوفيك لحوض وادي كاي براخ الذي يقع شمال العراق في محافظة دهوك وبالتحديد في ناحية السندي التابعة لقضاء زاخو والبالغ مساحته (187.37كم2)، ويعتمد هذا النموذج في تطبيقه على درجات الحرارة والأمطار والغطاء النباتي والتربة والانحدار وتم دمج جميع هذه المعطيات في برنامج ((ARC GIS 10.4.1 باستعمال صيغ رياضية وذلك لغرض الحصول على مستويات التعرية. وتبين من خريطة التعرية المحتملة لحوض وادي كاي براخ أن أكثر من (93.65%) من مساحة الحوض تقع ضمن نطاق التعرية الشديدة والشديدة جدا وهذا يتفق مع الانحدارات المتوسطة والقوية الخالية من الغطاء النباتي، كما اتضح من تطبيق معادلة نموذج جافريلوفيك أن الحوض يحتوي على ثلاثة أنواع من التعرية وهي (المتوسطة والشديدة والشديدة جدا) وبلغت مساحتهم (1.26، 49.05، 137.06 كم2) على التوالي وقد غطت التعرية الشديدة جدا أكثر من ثلثي مساحة الحوض. The research aims to use remote sensing data and geographic information systems software to model maps to estimate the extent of water erosion according to the Gavrilovic method for the Kai Brakh valley basin, which is located in northern Iraq in Dohuk Governorate, specifically in the Sindi district of Zakho District, which has an area of (187.37 km2). This model is adopted in It was applied to temperature, rainfall, vegetation cover, soil, and slope, and all of these data were integrated into the program (ARC GIS 10.4.1) using mathematical formulas for the purpose of obtaining erosion levels. The map of potential erosion of the Kai Brakh Valley Basin showed that more than (93.65%) of the basin area falls within the range of severe and very severe erosion, and this is consistent with moderate and strong slopes devoid of vegetation. It was also clear from applying the Gavrilovic model equation that the basin contains three types levels of erosion are (moderate, severe, and very severe), and their areas reached (1.26, 49.05, and 137.06 km2), respectively. The very severe erosion covered more than two-thirds of the. area of the basin
Keywords: جغرافيا التربة -- الاستشعار عن بعد -- درجات الحرارة -- الغطاء النباتي